Prioritising the role of community health workers in the COVID-19 response. Issue 6 (4th June 2020) - Ballard, Madeleine; Bancroft, Emily; Nesbit, Josh; Johnson, Ari; Holeman, Isaac; Foth, Jennifer; Rogers, Debbie; Yang, Jane; Nardella, James; Olsen, Helen; Raghavan, Mallika; Panjabi, Raj; et al.
Abstract : COVID-19 disproportionately affects the poor and vulnerable. Community health workers are poised to play a pivotal role in fighting the pandemic, especially in countries with less resilient health systems. Drawing from practitioner expertise across four WHO regions, this article outlines the targeted actions needed at different stages of the pandemic to achieve the following goals: (1) PROTECT healthcare workers, (2) INTERRUPT the virus, (3) MAINTAIN existing healthcare services while surging their capacity, and (4) SHIELD the most vulnerable from socioeconomic shocks. While decisive action must be taken now to blunt the impact of the pandemic in countries likely to be hit the hardest, many of the investments in the supply chain, compensation, dedicated supervision, continuous training and performance management necessary for rapid community response in a pandemic are the same as those required to achieve universal healthcare and prevent the next epidemic.